ADVANCES IN THE MEASUREMENT OF FUNDAMENTAL CONSTANTS - Gurikar, Shivaraj G (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Advances in the measurement of fundamental constants have played a pivotal role in refining our understanding of the physical universe. Fundamental constants, such as the speed of light (c), the gravitational constant (G), Planck’s constant (h), and the charge of the electron (e), are crucial for the accuracy of scientific theories and models across various fields, from particle physics to cosmology. Recent innovations in experimental techniques, instrumentation, and quantum technologies have enabled significantly improved measurements of these constants, contributing to greater precision in scientific research and the redefinition of SI units. A landmark achievement in this area was the redefinition of the International System of Units (SI) in 2019, where key units, including the kilogram and the ampere, were redefined based on fixed values of fundamental constants. This development eliminated reliance on physical artifacts, ensuring greater stability and universality in measurements. Notable advancements include the use of Kibble balances for determining Planck’s constant and optical lattice clocks for measuring time with unprecedented precision. Quantum technologies, such as quantum sensors and optical frequency standards, have also revolutionized fundamental constant measurements by providing greater sensitivity and accuracy. Techniques such as atom interferometry and quantum entanglement have made it possible to refine constants like the fine-structure constant (α) and the gravitational constant (G), while also testing their potential variations across space and time. These advances not only improve the precision of current measurements but also open new avenues for exploring potential new physics beyond the Standard Model. Continued progress in measurement techniques promises to deepen our understanding of the universe, providing valuable insights into the fundamental laws that govern the natural world.